Licenciamento ambiental em números: uma comparação entre as UHEs Santo Antônio, Jirau e Belo Monte - Rodrigues, Luiza Antonaccio Lessa (2019)
This work presents a diagnosis of the environmental licensing procedure of the Hydropower Plants (HPPs) of Santo Antônio, Jirau and Belo Monte. Understanding the differences between how the law foresees the procedure and how it works in a practical order is relevant to not only gather data on this subject, and identify the licensing procedure bottlenecks, but mainly to have empirical information that can subsidy future proposals to change the legislation currently in force. To do that, it was selected four parameters to guide the diagnosis for the environmental licensing procedure: the observance of the environmental constraints foresaw in the environmental license, the penalties applied against the project developer, the judicial actions against the project developer and the environmental institution as well asthe observance of the Authorization for Vegetation Suppression purposes. These parameters where chosen because they were quantifiable, which allows a comparable metrics to analyze the information. Despite the observance of the licensing procedure as foresaw by law, the practical results is that the environmental obligations are not being properly respected. Monitoring and controlling are not enough to hold the project developers accountable for their environmental obligations.